A novel platform for attenuating immune hyperactivity using EXO‐CD24 in COVID‐19 and beyond. Issue 9 (13th July 2022) - Shapira, Shiran; Ben Shimon, Marina; Hay‐Levi, Mori; Shenberg, Gil; Choshen, Guy; Bannon, Lian; Tepper, Michael; Kazanov, Dina; Seni, Jonathan; Lev‐Ari, Shahar; Peer, Michael; Boubas, Dimitrios; et al.
Abstract: A small but significant proportion of COVID‐19 patients develop life‐threatening cytokine storm. We have developed a new anti‐inflammatory drug, EXO‐CD24, a combination of an immune checkpoint (CD24) and a delivery platform (exosomes). CD24 inhibits the NF‐kB pathway and the production of cytokines/chemokines. EXO‐CD24 discriminates damage‐from pathogen‐associated molecular patterns (DAMPs and PAMPs) therefore does not interfere with viral clearance. EXO‐CD24 was produced and purified from CD24‐expressing 293‐TREx™ cells. Exosomes displaying murine CD24 (mCD24) were also created. EXO‐CD24/mCD24 were characterized and examined, for safety and efficacy, in vitro and in vivo . In a phase Ib/IIa study, 35 patients with moderate–high severity COVID‐19 were recruited and given escalating doses, 10 8 –10 10, of EXO‐CD24 by inhalation, QD, for 5 days. No adverse events related to the drug were observed up to 443–575 days. EXO‐CD24 effectively reduced inflammatory markers and cytokine/chemokine, although randomized studies are required. EXO‐CD24 may be a treatment strategy to suppress the hyper‐inflammatory response in the lungs of COVID‐19 patients and further serve as a therapeutic platform for other pulmonary and systemic diseases characterized by cytokine storm. Synopsis: In 5% of COVID‐19 patients, 5–10 days from disease onset, there is rapid clinical deterioration due to the cytokine storm with no effective therapy. EXO‐CD24 is the new immunomodulator with promising efficacy without interfering with pathogen clearance. EXO‐CD24 is a novel platform that helps normalize immune activity. EXO‐CD24 may represent a new therapeutic opportunity to overcome the devastating effect of COVID‐19 and beyond. EXO‐CD24 leads to inhibition of tissue injury‐driven inflammation without interfering with pathogen‐induced immune activation. EXO‐CD24 is a targeted innovative technology, based on CD24‐enriched exosomes, delivered directly to the lungs to suppress the cytokine storm, and has broad applicability. Abstract : In 5% of COVID‐19 patients, 5–10 days from disease onset, there is rapid clinical deterioration due to the cytokine storm with no effective therapy. EXO‐CD24 is the new immunomodulator with promising efficacy without interfering with pathogen clearance.